Analysis of Factors Affecting Willingness to Pay Rates for Industrial Consumer Premium Services in Electricity Companies (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to determine the effect of product innovation on brand image, product quality on brand image, product quality on consumer preferences, consumer knowledge on consumer preferences, brand image on willingness to pay, and consumer preferences on willingness to pay at the electricity company. The survey was carried out on 150 industrial consumers in the Pekalongan City area. Analysis of the data used with the Structural Equation Model (SEM) method. The results show that product innovation does not affect brand image. The product can make an impact when considering its equity position as well as its competitive position. Product quality has a positive and significant impact on brand image. This is supported by the availability of backup supply facilities and the addition of Change Over Switch equipment. Product quality does not affect consumer preferences. The quality offered must be easy for consumers to understand so that they can provide alternative choices. Consumer knowledge has a positive and significant impact on consumer preferences. If consumers can understand well, it will strengthen consumer considerations to switch to premium services. Brand image does not affect the willingness to pay. The brand image must have good credibility for premium service products. Consumer preferences have a positive and significant impact on willingness to pay. The more confident consumers are about the services provided, the more feasible it is to switch services even though the price is more expensive.